PENGARUH KOMITMEN ORGANISASI DAN KETIDAKPASTIAN LINGKUNGAN TERHADAP HUBUNGAN PARTISIPASI ANGGARAN DENGAN SENJANGAN ANGGARAN PADA INDUSTRI MANUFACTUR DI GRESIK - Afif, Muhajir (GEMA EKONOMI, 2012)
of targets to be achieved by the department manager of a company in conducting a series of specific activities in the future. Budget is a management tool in allocating limited resources and funding resources of the organization to achieve goals. The budget requires certainty, whether the organization has been implementing what has been specified in the plan. It is therefore necessary to control, control regarding the implementation of policy, implementation and evaluation of the implementation of the corrective action being taken under the standard. Given the importance of the budget in an organization requires a company to translate the overall budget standards into the plan long-term goals and short-term goals.Research is by using a quantitative method aims to examine the effect of budgetary participation on the budget gap in manufacturing firms in Gresik, and examine the influence of organizational commitment, job involvement and environmental uncertainty on budget gap in manufacturing firms in Gresik.The test results in this study found that participation in the budget, organizational commitment, job involvement and environmental uncertainty together have a significant relationship to the budget gap shown by the F count of 6.078 (F table = 2.469). The magnitude of the influence of the five independent variables to the gap is equal to 67.9% which means that 32.1% influenced by other variables not included in this study.